PENGGUNAAN DAGING SAPI PADA RUMAH MAKAN PADANG DI KOTA BANDAR LAMPUNG - Erni Rohasti; Wuryaningsih Dwi Sayekti; Raden Hanung Ismono (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The objectives of this research were to analyze the importance level of processed beef according to consumers and the factors that affect the purchase of beef by Padang restaurants in Bandar Lampung City.  Research samples consisting of 55 restaurants selected randomly and 165 consumers selected by using accidental sampling. Data were analyzed descriptively and analitically using regression.  The result showed that beef becomes the second most important processed food after processed chicken. As many as 64 respondents (38,79%) stated that the processed beef menu was the most important, 21 respondents (12,73%) said the processed beef menu was equally important, and 80 respondents (48,48%) said the processed beef menu was less important.  However, the importance level of processed beef did not affect on the purchase of beef.  It was because, not all consumers who considered processed beef most important always buy beef.  The budget allocation for beef, the number of visitors, the number of processed beef kinds, and the total number of seats affected the purchase of beef by Padang restaurants in Bandar Lampung.   Key words: beef, importance level, restaurants